Dual Drive for Vertical Movement of Resonance Hopping Robot - Akinfiev, T.; Armada, M. (Штучний інтелект, 2010)
In the present study vertical movements of resonance hopping robot of special construction with one leg and dual drive are considered. The construction of hopping robot with compensation of losses during flight of the robot allows employing a simple control system and having a stable regime of its operation so that the robot has self-property to maintain a specified height of jumping. The data on dynamical calculation, simulations and experimental testing are discussed. The solution of the problem of actuator’s optimum parameters choice (including variable transmission ratio) for the considered robot is presented.